Research Conducted at the Site of T. Kosciuškos Street 1, Vilnius - Žvirblys, Atas (Archaeologia Lituana, 2025)
In the spring and summer of 2024, excavations carried out at the site located at 1 T. Kosciuškos Street in Vilnius revealed cultural layers dating from the late 13th to the 20th century, as well as remains of wooden structures dating back to the 13th–14th centuries. These findings provided new insights into the development of this part of Vilnius during the early stages of the city’s formation. Equally intriguing is the history of the site from the 17th to the 18th century, which is associated first with a manor estate that once stood there and, from the 19th century onwards, with the operation of a detention facility on the site. This article analyses the archaeological and historical contexts of these discoveries, presents the research results, and offers interpretations based on the collected data.
Keywords: Medieval Vilnius; Crooked castle; wooden structures; archaeology; detention facilities